Explaining export diversification through firm innovation decisions: The case of Brazil - Cirera, Xavier (2015)
This paper investigates a largely unexplored dimension of export performance, firm level determinants of export diversification. We extend innovation studies and enrich the export literature by analyzing the role of firms’ innovation and market strategies in explaining export diversification. To do so, we use a unique dataset that links data on exports, innovation and firms’ characteristics at the firm level in Brazil. Our findings show that access to existing resources, as emphasized by existing innovation studies on emerging economies, cannot account for all the heterogeneity observed in firm’s export diversification in Brazil. Innovative efforts and the strategic positioning of firms in the domestic market are crucially important in explaining diversification. These results emphasize the importance of distinguishing new from existing exports when investigating the dimensions that affect export performance.